TINGKAT KEPENTINGAN ELEMEN ARSITEKTURAL PADA VIHARA VAJRA BUMI KERTAYUGA BERDASARKAN PERSEPSI UMAT BUDDHISME ALIRAN TRUE BUDDHA SCHOOL - Wijaya, Candra; Kalsum, Emilya; Caesariadi, Tri Wibowo (JMARS: Jurnal Mosaik Arsitektur, 2025)
Architecture reflects the evolving needs of humanity, including within the spiritual context. Religion and belief system play a crucial role in shaping religious architecture, which not only serves as a place of worship but also embodies symbolic values and religious practices. The diverse religious traditions in Indonesia create a rich religious landscape, including in the architecture of places of worship such as monasteries (vihara). This research focuses on Vajra Bumi Kertayuga Monastery in Pontianak, a physical representation of the teachings of the True Buddha School sect. The evaluation of its architectural elements aims to assess the alignment between the building"™s design and the spiritual values of the True Buddha School sect, and how these elements influence the spiritual experiences of visitors. Theoretical approaches concerning architectural elements provide the basis for analyzing the harmony between philosophical teachings, worship practices, and the physical design of the monastery. This study is expected to offer valuable insights for the development and maintenance of monasteries, ensuring they continue to support optimal religious practices.The research employs a descriptive-quantitative approach using surveys to collect numerical data. Data was gathered through questionnaires distributed to members of Vihara Vajra Bumi Kertayuga to evaluate the perceived importance of architectural elements from the perspective of True Buddha School adherents. Respondents were selected randomly using a simple random sampling technique to represent a broader population. Collected data was analyzed statistically to identify patterns and relationships in perceptions regarding the alignment of the vihara's architectural elements with its teachings.The findings indicate that the architectural elements of Vihara Vajra Bumi Kertayuga"”including interior layout, facade, ceiling, flooring, columns, doors, windows, walls, and stairs"”hold varying levels of importance. Generally, respondents rated the interior layout and facade as the most crucial in creating a religious atmosphere conducive to worship for True Buddha School adherents. Among the 31 respondents who worship at the vihara, the interior layout, facade, and ceiling were identified as playing the most significant roles in supporting worship activities. Flooring, columns, windows, and walls were considered moderately important, while doors and stairs were deemed to have lower significance. Respondents also highlighted that the form, ornamentation, size, and color of architectural elements significantly contribute to creating a religious ambiance and supporting worship, whereas the materials and textures of these elements were perceived as less critical.